Shadow Economies and Corruption All Over the World: New Estimates for 145 Countries - Friedrich G. Schneider (Economics: The Open-Access, Open-Assessment E-Journal, 2007)
Estimations of the shadow economies for 145 countries, including developing, transition and highly developed OECD economies over 1999 to 2005 are presented. The average size of the shadow economy (as a percent of "official" GDP) in 2004/05 in 96 developing countries is 36.7%, in 25 transition countries 38.8% and in 21 OECD countries 14.8%. An increased burden of taxation and social security contributions, combined with a labour market regulation are the driving forces of the shadow economy. Furthermore, the results show that the shadow economy reduces corruption in high income countries, but increases corruption in low income countries. Finally, the various estimation methods are discussed and critically evaluated.
Keywords: H11; H26; O17; O5; D78; H2; 330; shadow economy of 145 countries; tax burden; tax moral; quality of state institutions; regulation; DYMIMIC and other estimation methods; Schattenwirtschaft; Steuerbelastung; Steuermoral; Wirtschaftswachstum; Übergangswirtschaft; Schätzung; Welt; Entwicklungsländer; Osteuropa; OECD-Staaten